Leucemia linfoblástica aguda em gata - Relato de caso - Léga, Elzylene; Pinto, Mildre Loraine; Galvão, André Luiz Baptista [UNESP]; De Vasconcellos, Amanda Leal [UNESP]; Neto, Nassim Madi (My University, 2013)
The presence of atypical cells or bizarre or disorganized group of immature cells in blood smears and persistent and unexplained increase of a specific cell type in peripheral blood may be suggestive of leukemia. Dogs and cats with leukemia have moderate to sever leukocytosis, erythrocyte counts and platelet counts in peripheral blood may be diminished. Examination of the bone morrow aspirates may be important for confirmation and determination of prognosis in leukemia. To describe a case of acute lymphoblastic leukemia (ALL) in a cat, not spayed, SRD, four years old is the goal of this work.
Acute lymphoblastic leukemia in cat - Case report
Keywords: Anemia; Lymphocytes; Thrombocytopenia